Damaging flood risk in the Portuguese municipalities - Santos, Pedro Pinto (2018)
Modeling and understanding the impact of climate change on flooding processes in Mediterranean climate areas, namely in southern Europe, is a complex endeavor, which must also consider exposure and vulnerability patterns. Assuming that vulnerability plays a relevant role in explaining the degree of loss due to natural hazards, the present research compares a flood-susceptibility index with a social-vulnerability index and a historical record of flood losses, both aggregated at the municipal level. The purpose of this research is to define municipal flood risk profiles that would rank the 278 municipalities and contribute to the strategic allocation of resources and flood risk management [...]